The Effect of Sheep Feces Compost with Different Fertilization Doses and Intervals on the Productivity of Mixed Pastures (Clitoria ternatea and Brachiaria ruziziensis) - Purba, Dea Ade Yoan; Ginting, Nurzainah; Yunilas; Alwiyah (Talenta Publisher, 2021)
Mix pasture contains more complete nutrition for animal feed. This study aims to determine the effect of giving sheep feces compost with different fertilization doses and intervals on the productivity of mixed pastures (Clitoria ternatea and Brachiaria ruziziensis). This research was conducted in Kotangan Village, Kec. Galang, Kab. Deli Serdang North Sumatra from September to November 2020. The experimental design was used a split-plot design with two treatment factors and three replications. Factor I is the main plot, namely the fertilization interval: N1 = once every four weeks and N2 = once every two weeks. Factor II as a subplot which were doses of compost : P0 = control (without compost), P1 = compost 1 kg/plot (10 t/h), P 2 = compost 2 kg/plot (20 t/h) and P3 = compost 3 kg/plot (30t/h).The variables observed were plant height, number of leaves, number of tillers, number of branches, fresh production, dry matter, crude protein, and crude fiber. The results showed that sheep feces compost doses and different time intervals for fertilization had a significant effect (P<0,05 ) on the number of leaves and tillers of Brachiaria ruziziensis, crude protein, and coarse fiber of mixed pasture. There was no significant effect (P>0,05) on plant height, the number of leaves and number of branches of Clitoria ternatea, the height of Brachiaria ruziziensisas, and fresh and dry mixed pasture production. The appropriate fertilization interval was once every two weeks, and the best fertilizer dose was 3 kg/plot (30 t/h).